Attention-dependent reductions in burstiness and action potential height in macaque area V4 - Anderson, Emily B. (2013)
Attention improves the encoding of visual stimuli. One mechanism that is implicated in facilitating sensory encoding is the firing of action potentials in bursts. We tested the hypothesis that when spatial attention is directed to a stimulus, this causes an increase in burst firing to the attended stimulus. To the contrary, we found an attention-dependent reduction in burstiness among putative pyramidal neurons in macaque area V4. We accounted for this using a conductance-based Hodgkin-Huxley style model in which attentional modulation stems from scaling excitation and inhibition. The model exhibited attention-dependent increases in firing rate and made the surprising and correct prediction that when attention is directed into a neuron’s receptive field, this reduces action potential height. The model thus provided a unified explanation for three distinct forms of attentional modulation, two of them novel, and implicates scaling of the responses of excitatory and inhibitory input populations in mediating attention.